Operating EC-based Electrolytes with Li- and Mn-Rich NCMs: The Role of O2-Release on the Choice of the Cyclic Carbonate. Issue 11 (1st July 2020) - Teufl, Tobias; Pritzl, Daniel; Krieg, Patrick; Strehle, Benjamin; Mendez, Manuel A.; Gasteiger, Hubert A.
Abstract : Li- and Mn-rich layered oxides are a promising class of cathode active materials (CAMs) for future lithium-ion batteries. However, they suffer from fast capacity fading in standard EC-containing electrolytes, and therefore fluorinated alternatives, such as FEC, are required to improve their full-cell performance, which unfortunately increases the cost of the electrolyte. In this study, we will analyze the reasons for the poor cycling performance of EC-containing electrolytes with CAMs that release lattice oxygen at high degrees of delithiation, i.e., either of Li- and Mn-rich NCMs (LMRNCMs) during activation or of NCMs at high cutoff voltages. By on-line electrochemical mass spectrometry (OEMS), we will show that the stability of EC towards electrochemical oxidation is sufficient up to potentials of ≈4.7 V vs Li + /Li, but that its chemical reaction with lattice oxygen released from CAMs negatively affects cycle-life. Furthermore, we will show that the use of EC-based electrolytes above the onset potential for oxygen release leads to a resistance build-up causing a rapid "rollover" fading, while FEC does not show such a dramatic impedance increase. Last, we will demonstrate that the lattice oxygen release from NCM-622 above ≈4.5 V vs Li + /Li requires the use of EC-free electrolytes for stable cycling.